Putting amazing back into Grace who does what in salvation - Horton, Michael Scott; Christians United for Reformation (CURE) (Grand Rapids, MI Baker, 1994)
Includes bibliographical references.
Keywords: Salvation -- biblical teaching; Grace (theology) -- biblical teaching